(untitled) (The Pakistan Development Review, 2003)
Three main factors that contribute to agricultural growth are the increased use of agricultural inputs, technological change and technical efficiency. Technological change is the result of research and development efforts, while technical efficiency with which new technology is adopted and used more rationally is affected by the flow of information, better infrastructure, availability of funds and farmers’ managerial capabilities. Higher use and better mix of inputs also requires funds at the disposal of farmers. These funds could come either from farmers’ own savings or through borrowings. In less developed countries like Pakistan where savings are negligible especially among the small farmers, agricultural credit appears to be an essential input along with modern technology for higher productivity. Credit requirements of the farming sector have increased rapidly over the past few decades resulting from the rise in use of fertiliser, biocides, improved seeds and mechanisation, and hike in their prices. The agricultural credit system of Pakistan consists of informal and formal sources of credit supply. The informal sources include friends, relatives, commission agents, traders and private moneylenders etc. Presently, the formal credit sources are comprised of financial institutions like Zarai Taraqiati Bank Limited (ZTBL)—formerly known as Agricultural Development Bank of Pakistan (ADBP), Commercial Banks, and Federal Bank for Cooperatives. Recently, some non-government organisations (NGOs) are also advancing agricultural credit to the rural communities.